Violência verbal, intertextualidade e referenciação em comentários do Instagram - Simoes, Wemerson (2020)
This study seeks to investigate, in a sociocognitive and interactional perspective, comments constructed in posts from the social network Instagram, in order to verify the functions of intertextuality and referencing for the establishment and maintenance